2023
DOI: 10.2340/jrm.v55.4405
|View full text |Cite
|
Sign up to set email alerts
|

Home-based telerehabilitation for community-dwelling persons with stroke during the COVID-19 pandemic: A pilot study

Abstract: Objectives: To determine the feasibility and safety of use of asynchronous telerehabilitation for community-dwelling persons with stroke in the Philippines during the COVID-19 (SARS-CoV-2) pandemic, and to evaluate the change in participants’ telerehabilitation perceptions, physical activity, and well-being after a 2-week home-based telerehabilitation programme using a common social media application.Design: Pilot study.Participants: Nineteen ambulatory, non-aphasic adult members of a national university hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Carl FROILAN D. LEOCHICO, PTRP, MD 1,2 From the 1 Department of Physical Medicine and Rehabilitation, St. Luke's Medical Center, Global City and Quezon City, Philippines, and 2 Department of Rehabilitation Medicine, Philippine General Hospital, University of the Philippines Manila, Manila, Philippines. E-mail: cfdleochico@stlukes.com.ph is invaluable in advancing scholarly discourse, and I welcome the chance to clarify and expand upon the ideas presented in our article.…”
Section: Response To the "Commentary On: Home-based Telerehabilitatio...mentioning
confidence: 99%
See 4 more Smart Citations
“…Carl FROILAN D. LEOCHICO, PTRP, MD 1,2 From the 1 Department of Physical Medicine and Rehabilitation, St. Luke's Medical Center, Global City and Quezon City, Philippines, and 2 Department of Rehabilitation Medicine, Philippine General Hospital, University of the Philippines Manila, Manila, Philippines. E-mail: cfdleochico@stlukes.com.ph is invaluable in advancing scholarly discourse, and I welcome the chance to clarify and expand upon the ideas presented in our article.…”
Section: Response To the "Commentary On: Home-based Telerehabilitatio...mentioning
confidence: 99%
“…We have read the article by Carl Froilan D. Leochico et al (1) with great interest but have also found some points that need further clarification.…”
mentioning
confidence: 93%
See 3 more Smart Citations